Identification of Linkages between the Competitive Potential and Competitive Position of SMEs Related to their Internationalization Patterns Shortly after the Economic Crisis - Piotr Trąpczyński; Barbara Jankowska; Marlena Dzikowska; Marian Gorynia (Entrepreneurial Business and Economics Review)
Objective: We aim to identify the most advanced SMEs in terms of their internationalisation shortly after the end of the economic crisis. For this purpose we look at the changes in the intensity of internationalisation in terms of its breadth and depth. Research, Design & Methods: The study is based on a complementary data set derived from secondary (AMADEUS database) and primary sources of information (computer assisted telephone interviews with top managers) for 553 micro, small and medium firms located in Poland. We conduct a cluster analysis to identify different internationalization profiles of SMEs for the years 2010-2013. Findings: In the year of the global economic crisis ambitious investors on average had at their disposal substantially better competitive potential than the remaining two groups. Ambitious exporters were better equipped than cautious internationalizers only in terms of human resources, intangible resources and quality control. Implications & Recommendations:  Policy support should be particularly oriented towards supplying information about foreign markets and fostering firms in an optimal allocation of their resources. Contribution & Value Added: The study suggests that the strategy of diversifying international markets during the economic crisis and recovery can be a means of improving performance and reducing excessive dependence on fluctuations in key markets.